Layer-by-layer nanofiber-enabled engineering of biomimetic periosteum for bone repair and reconstruction. (November 2018) - Wang, Tao; Zhai, Yuankun; Nuzzo, Marc; Yang, Xiaochuan; Yang, Yunpeng; Zhang, Xinping
Abstract: Periosteum plays an indispensable role in bone repair and reconstruction. To recapitulate the remarkable regenerative capacity of periosteum, a biomimetic tissue-engineered periosteum (TEP) was constructed via layer-by-layer bottom-up strategy utilizing polycaprolactone (PCL), collagen, and nano-hydroxyapatite composite nanofiber sheets seeded with bone marrow stromal cells (BMSCs). When combined with a structural bone allograft to repair a 4 mm segmental bone defect created in the mouse femur, TEP restored donor-site periosteal bone formation, reversing the poor biomechanics of bone allograft healing at 6 weeks post-implantation. Further histologic analyses showed that TEP recapitulated the entire periosteal bone repair process, as evidenced by donor-dependent formation of bone and cartilage, induction of distinct CD31 high type H endothelium, reconstitution of bone marrow and remodeling of bone allografts. Compared to nanofiber sheets without BMSC seeding, TEP eliminated the fibrotic tissue capsule elicited by nanofiber sheets, leading to a marked improvement of osseointegration at the compromised periosteal site. Taken together, our study demonstrated a novel layer-by-layer engineering platform for construction of a versatile biomimetic periosteum, enabling further assembly of a multi-component and multifunctional periosteum replacement for bone defect repair and reconstruction.